The Inefficiency of Market Transparency – A Model with Endogenous Entry - Yiquan Gu; Burkhard Hehenkamp (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Including the entry decision in a Bertrand model with imperfectly informed consumers, we introduce a trade-off at the level of social welfare. On the one hand, market transparency is benefi cial when the number of firms is exogenously given. On the other, a higher degree of market transparency implies lower profits and hence makes it less attractive to enter the market in the first place. It turns out that the second effect dominates: too much market transparency has a detrimental effect on consumer surplus and on social welfare.
Keywords: D43; L13; L15; 330; market transparency; endogenous entry; homogenous products